Preparation and characterization of polyvinyl alcohol- graphene oxide/poly(3,4-ethylenedioxythiophene) composite nanofiber - Zubair, Nur Afifah (2016)
Electrically conductive nanofibers are nanostructured materials which attracted extensive interest for their superior properties. These materials are being studied in various research fields include, electrochemistry, material science and electronic applications. In this work, conducting nanofibers composed of polyvinyl alcohol (PVA), graphene oxide (GO) and poly(3,4-ethylenedioxythiophene) (PEDOT) were fabricated via a combined method using electrospinning and electropolymerization techniques. During electrospinning, the concentration of PVA or PVA-GO solution, and the applied voltage were deliberately altered in order to determine the optimized electrospinning conditions. The optimized parameters with 0.1 mg/mL of GO and 10 w/v% of PVA concentration with electrospinning voltage of 15 kV were obtained. The electrospun PVA and PVA-GO nanofiber mats were further modified by coating with the conjugated polymer, PEDOT using electropolymerization techniques which is a facile approach for coating the nanofibers. SEM images of the obtained nanofibers revealed that PEDOT grew well on the surface of the electrospun nanofibers during the potentiostatic mode of the electropolymerization process. The presence of GO and PEDOT in nanofiber was confirmed by FTIR and Raman spectroscopy analyses. The optimum electropolymerization of PEDOT was at potential of 1.2 V in 5 mins. The electrochemical measurements demonstrated that the PVA–GO/PEDOT composite nanofiber could enhance the current response and reduce the charge transfer resistance of the nanofiber. The equivalent circuit models were used to fit the impedance spectra of PEDOT, PVA/PEDOT and PVA-GO/PEDOT nanofibers where the spectra were fitted well.